Electroretinography and immunohistochemistry of retina in rabbits treated with sildenafil citrate - Amaral, A. V.C.; Silva, G. A. [UNESP]; Costa, A. P.A.; Oliveira, K. S.; Jordão, P. [UNESP]; Ribeiro, A. P.; Renzo, R. [UNESP]; Laus, J. L. [UNESP] (FapUNIFESP (SciELO), 2015)
Sildenafil citrate is a type-5 phosphodiesterase inhibitor (PDE-5), able to inhibit type-6 phosphodiesterase (PDE-6) as well, providing clinical benefits and paraeffects, some of them potentially related to the retina. The effects of the sildenafil on the retrobulbar and retinal circulation were studied in 27 adult male rabbits of the White New Zealand breed. The electric activity of the retina was evaluated before and at the end of the treatments, and immunohistochemistry studies were conducted. An amplitude increase of the b wave was found in the mixed response of cones and rods after 7 days of treatment with sildenafil citrate. However, in the other evaluations and periods, the values did not differ from the basal ones. Through immunohistochemistry, no significant decrease of the expression of PDE-5 and PDE-6 proteins was observed. Based on the results obtained, it is possible to admit that the sildenafil citrate did not change the expression of PDE-5 and PDE-6, neither the electroretinographic activity of the retina of male rabbits of the White New Zealand breed.
Keywords: Electroretinography; Immunohistochemistry; Rabbit; Sildenafil citrate